Partisipasi masyarakat dalam kegiatan kampung tangguh untuk mengantisipasi penyebaran Covid-19 di Kota Surabaya - Hermanto Hermanto; Endang Susilowati; Sukriyah Kustanti; Siti Zahrok; Dian Eka Savitri; Daffa Rahman Hermannas (Unri Conference Series: Community Engagement, 2021)
The Covid-19 pandemic has had a tremendous impact on various sectors of human life. The government has made various rules and policies in dealing with pandemics and the impacts they cause but are more top-down and common which often do not touch on substantive things in accordance with real conditions in the local community. On the contrary, local communities that better understand their environmental situation and conditions are often not involved in determining the rules and policies in addressing this pandemic. Kampung Tangguh as an effort by the community to survive during a pandemic is a form of local wisdom-based community involvement in the community itself in helping the government overcome the Covid-19 pandemic and the impact it causes. Using a qualitative approach through field reviews, interviews, and documentation studies, this paper illustrates the form of community participation in addressing the Covid-19 pandemic. From the results of this study, it is seen that people at the village level or the neighborhood where they live can actively participate together in overcoming the spread and impact of Covid-19.